CROSS-AMPLIFICATION OF AQUILARIA CRASSNA MICROSATELLITE DNA MARKERS IN TWO OTHER CLOSELY RELATED AGARWOOD SPECIES (A. MALACCENSIS AND A. MICROCARPA) - Irmayanti, Laswi; Dwiyanti, Fifi Gus; Rachmat, Henti Hendalastuti; Yulita, Kusumadewi Sri; Siregar, Iskandar Z. (Indonesian Journal of Forestry Research, 2025)
Agarwood is a distinctive wood resin product extracted from the important genus of Aquilaria, but the population of agarwood-producing trees from natural forests in Indonesia is threatened due to over-exploitation, leading to an urgent call for conservation and sustainable uses. Molecular techniques such as DNA profiling have been used to ensure the legality, conservation, and sustainability of species from this genus. In this study, cross-species amplification of microsatellite markers initially developed for Aquilaria crassna was developed on two other closely related agarwood species (Aquilaria malaccensis and A. microcarpa), and their genetic variation was evaluated. The four loci (6pa18, 10pa17, 16pa17, and 71pa17) were used to amplify leaf genomic DNA from 55 trees across three Aquilaria species. The results showed that the four loci could successfully be amplified in A. malaccensis, A. microcarpa, and A. crassna. In addition, A. crassna exhibited higher genetic variation (Na=2.75, Ne=2.35, He= 0.5672, and F=-0.727) than A. malaccensis (Na=2.75, Ne=2.19, He=0.5424, and F=-0.598) and A. microcarpa (Na=2.50, Ne=2.11, He= 0.5234, and F=-0.734) indicated the transferability of microsatellite markers in closely related agarwood species, possibly due to the flanking region in these four microsatellite regions being well-conserved in several agarwood species. These findings indicated that the markers tested here can be considered an effective tool for future studies in population and conservation genetics to support the management of agarwood genetic resources and track its supply chain to prevent overexploitation.